Twist extrusion: review - Beygelzimer, Y.; Varyukhin, V.; Kulagin, R.; Orlov, D. (Физика и техника высоких давлений, 2015)
The review of research on the twist extrusion (TE) made in Donetsk Institute for Physics and Engineering of National Academy of Sciences of Ukraine since 1999 is reported. The main features of twist extrusion are presented. It is noted Twist Extrusion has a significant commercial potential due to the following physical effects: intensive grain refinement; homogenization and mixing; intensive consolidation of powders. The engineering relations for the major Twist Extrusion characteristics are obtained. The progress in practical application of this process is shown. Представлено огляд досліджень з гвинтової екструзії (ГЕ), виконаних у ДонФТІ починаючи з 1999 р. Показано, що ГЕ має значний комерційний потенціал у зв’язку з наступними фізичними ефектами: інтенсивним подрібненням структури матеріалів; гомогенізацією і перемішуванням на різних масштабних рівнях; інтенсивною консолідацією порошкових матеріалів. Наведено інженерні співвідношення для основних характеристик ГЕ. Показано прогрес у практичному застосуванні ГЕ. Представлен обзор исследований по винтовой экструзии (ВЭ), выполненных в ДонФТИ начиная с 1999 г. Показано, что ВЭ имеет значительный коммерческий потенциал в связи со следующими физическими эффектами: интенсивным измельчением зеренной структуры материалов; гомогенизацией и перемешиванием на различных масштабных уровнях; интенсивной консолидацией порошковых материалов. Приведены инженерные соотношения для основных характеристик ВЭ. Показан прогресс в практическом применении ВЭ.